Tanning addiction: conceptualization, assessment and correlates. (24th August 2018) - Andreassen, C.S.; Pallesen, S.; Torsheim, T.; Demetrovics, Z.; Griffiths, M.D.
Summary: A number of recent studies suggest that tanning has the potential to be addictive. Tanned skin is often viewed as more attractive than untanned skin, and being tanned has been associated with increased energy and self‐confidence. Additionally, sunbathing has been shown to provide pleasant feelings of warmth and relaxation to most individuals. However, sunbathing and tanning to excess are associated with an increased risk of a variety of health problems, such as skin cancers and specific eye diseases. Excessive tanning can be linked to a number of mental health disorders, such as obsessive‐compulsive behaviours, body dysmorphic disorder and impulsive control disorders. Still, much evidence suggests that excessive tanning should be regarded as a behavioural addiction, and this study describes a new, brief screening tool for assessing tanning addiction. In this study, a web‐based survey was published in the online edition of five nationwide Norwegian newspapers during March to May 2014. Questions addressed criteria that are used to diagnose addiction, and included preoccupation with tanning, tanning improving mood, more tanning being required in order to be satisfied, and restlessness or negative feelings when not tanning. People were asked about the past month and the response format adhered to a 5‐point Likert scale (from 0=never to 4=always). The new system, called the Bergen Tanning Addiction Scale, requires further testing but performed well. Tanning addiction was associated with being female, not being in a relationship, extroversion, neuroticism, anxiety and obsessive‐compulsiveness. Abstract : Linked Article:  Andreassen et al. Br J Dermatol 2018;179 :345–352